Response of bird community to oil palm plantation and agroforestry in Dramaga campus IPB University, West Java, Indonesia - Syahras Fathin Aminuddin; Lintang Yodhy; Heri S. Yunus; Moh. Reza Sese Sese; M. Dhiya’ur Rachman Rachman; Rizki Amaliah; Puji Rianti; Windra Priawandiputra; Tri Atmowidi (Treubia, 2026)
As oil palm plantations continue to grow and become a mainstay commodity in Indonesia,unfortunately, this also has an environmental impact that can threaten bird communities. On the otherhand, the agroforest system is considered to be able to preserve the richness of bird species comparedto other monoculture plantations. This study analyzes how bird communities' response in oil palmplantation and agroforestry habitats is compared based on diversity, composition, species similarity,feeding guilds, and bird space use. This study was conducted at the Kebun Pendidikan Cikabayan (KPC)in the oil palm plantation area and the Taman Hutan Kampus (THK) in the IPB Dramaga campusagroforestry area, using transect, count point and vantage point methods from September to October2023. A total of 42 species belonging to 28 families were dominated by forest generalists, followed byopen habitat generalists, forest specialists, and forest edge species, 50% of which were insectivores. Thedaily activities of the dominant species in both locations showed differences between the use of spacein THK and KCP. Based on the diversity and evenness values, the THK location (H’= 2.95; E= 0.85)has a higher value than KPC (H’= 2.62; E= 0.78), although it is still in the same diversity category,namely moderate (H’= 2.5-2.9 in the moderate category). The species similarity index value also showsa species similarity of 75% between the two locations. Due to its relatively high diversity and potentialcarrying capacity for forest-dependent species in forest-agricultural landscapes, this area needs to bepreserved and its habitat quality improved planting native tree species with tall, hard stems that arefavored by hollow-nesting birds and food trees such as Ficus spp.